A hyperboloid structure as a mechanical model of the carbon bond. (1st October 2016) - Berinskii, I.E.; Krivtsov, A.M.
Abstract: We present a new mechanical model of interatomic bonds, which can be used to describe the elastic properties of the carbon allotropes, such as graphite, diamond, fullerene, and carbon nanotubes. The interatomic bond is modeled by a hyperboloid–shape truss structure. The elastic characteristics of this bond are determined. Previous known structural models also used elastic elements (beams, trusses) to simulate a carbon bond. However unlike them our model satisfies to the correct ratio of the longitudinal and lateral stiffness, observed from the previous experimental and theoretical results. Parameters of the bond in application for graphene and diamond were determined.